Prolonged alpha-blockade and doxazosin are associated with hypertensive crisis in pheochromocytoma surgery - Zawadzka, Karolina; Pisarska-Adamczyk, Magdalena; Hubalewska-Dydejczyk, Alicja; Pędziwiatr, Michał (Frontiers in Endocrinology, 2026)
ObjectiveHypertensive crisis represents a significant intraoperative challenge in pheochromocytoma surgery, often necessitating immediate pharmacologic intervention. To reduce this risk, preoperative α-adrenergic blockade is routinely implemented. Although prior studies have addressed the choice of α-blockade, the impact of its type, treatment duration, and final titrated dose on hypertensive crisis has not yet been established.MethodsA retrospective analysis was conducted on 110 patients undergoing laparoscopic adrenalectomy for pheochromocytoma. The type of alpha-blocker (doxazosin: DOX vs. phenoxybenzamine: PXB), duration of preoperative preparation, and final titrated dose were evaluated regarding their impact on the risk and duration of intraoperative hypertensive crisis (SBP >200 mmHg).ResultsThe duration of hypertensive crisis was significantly longer in the DOX group (median 15.0 (10.0-30.0) vs. 10.0 (5.0-15.0 min, p=0.03). The DOX group demonstrated higher intraoperative vasopressor use (39.6% vs. 10.9%, p<0.001), and a longer perioperative hospitalization compared to the PXB group (median 3.0 (2.2-4.0) vs 2.0 (2.0-3.0), p<0.001). Diabetes, urinary metanephrines >10× ULN, and preoperative α-blockade >30 days were independent risk factors for hypertensive crisis. Prolonged blockade was linked to longer crisis duration and increased vasopressor use, particularly with DOX. The final α-blocker dose did not influence hypertensive outcomes.ConclusionSelective α-blockade with doxazosin resulted in longer hypertensive crises, increased intraoperative vasopressor requirements, and prolonged hospitalization. Prolonged α-blockade (>30 days) was associated with more frequent and prolonged hypertensive crises and a higher risk of postoperative vasopressor use.